Об эффективности применения неприводного инструмента в процессах валковой формовки - Ахлестин, А. В. (My University, 2009)
Приведены данные о величине и распределении скоростей при подгибке полки швеллера формующими элементами разной конструкции. Для каждой из них определены оптимальные диапазоны углов подгибки. Показаны преимущества формовки в клетях с боковыми цилиндрическими роликами.

The data’s on magnitude and distribution of speeds are reduced at a camber of a shelf of a channel section by molding elements of a different construction. For each of them the optimum ranges of corners of a camber are defined. Is shown, that most effective is the forming of roll-formed shapes in mills containing side cylindrical rollers.
Keywords: скорость; энергозатраты; качество; крутящий момент; instrument; roll-forming; effective; speed; expenditure of energy; quality